Laying an Early Foundation: Lifestyle Medicine Pre-Professional Education (LMPP) Member Interest Group. Issue 5 (September 2020) - Merlo, Gia; Tollefson, Michelle; Dacey, Marie; Lenz, Thomas; Luchsinger, Mary; Muscato, Dennis; Frates, Elizabeth Pegg
Just as lifestyle medicine is the necessary foundation for true health care reform, lifestyle medicine competencies should be the foundation for health education. Although lifestyle medicine education may benefit a health professional at any stage in their education or career, evidence-based undergraduate lifestyle medicine education for future health professionals shifts the perspective of health and health care delivery. Educating health preprofessionals in associate, bachelor's, master's, and other preprofessional healthcare training programs is of paramount importance due to the interdisciplinary nature of lifestyle medicine. To accomplish this, American College of Lifestyle Medicine (ACLM) members can work collaboratively through committees, projects, and working groups—becoming leadership champions of change. An ACLM Pre-Professional Member Interest Group (LMPP) was created in 2018. LMPP has been working to build a national collaborative effort to amass, create, and distribute resources for educators in this pre-professional arena. Educating college students planning to become professionals outside the medical sphere, for example, lawyers, business people, artists, and engineers, will also benefit the field by introducing the power of nutrition, exercise, sleep, social connection, and stress resiliency during this formative state of career development. Pre-professional educational programs provide learners the opportunity to personally experience the power of lifestyle medicine.